2015
DOI: 10.1128/aem.03949-14
|View full text |Cite
|
Sign up to set email alerts
|

Piliation of Lactobacillus rhamnosus GG Promotes Adhesion, Phagocytosis, and Cytokine Modulation in Macrophages

Abstract: dRecently, spaCBA-encoded pili on the cell surface of Lactobacillus rhamnosus GG were identified to be key molecules for binding to human intestinal mucus and Caco-2 intestinal epithelial cells. Here, we investigated the role of the SpaCBA pilus of L. rhamnosus GG in the interaction with macrophages in vitro by comparing the wild type with surface mutants. Our results show that SpaCBA pili play a significant role in the capacity for adhesion to macrophages and also promote bacterial uptake by these phagocytic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(57 citation statements)
references
References 67 publications
3
51
0
1
Order By: Relevance
“…A. naeslundii might be less susceptible to OPN treatment due to the presence of type I/II fimbriae that extend up to 700 nm from the cell surface [17] and thereby potentially penetrate the adsorbed OPN layer. A. viscosus, Lactobacillus spp., and streptococci can also produce fimbriae or pili for adhesion [42][43][44][45][46], but the presence and length of such cell surface appendages vary considerably, even between different strains of the same species, and there is no information about pili or fimbriae production by the strains employed in this study. Alternatively, the observed differences might result from differential blocking of salivary receptors by OPN at low concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…A. naeslundii might be less susceptible to OPN treatment due to the presence of type I/II fimbriae that extend up to 700 nm from the cell surface [17] and thereby potentially penetrate the adsorbed OPN layer. A. viscosus, Lactobacillus spp., and streptococci can also produce fimbriae or pili for adhesion [42][43][44][45][46], but the presence and length of such cell surface appendages vary considerably, even between different strains of the same species, and there is no information about pili or fimbriae production by the strains employed in this study. Alternatively, the observed differences might result from differential blocking of salivary receptors by OPN at low concentrations.…”
Section: Discussionmentioning
confidence: 98%
“…(Ossowski et al ., ; Turroni et al ., ; Tytgat et al ., ; Ottman et al ., ). While adhesion to the epithelium and colonisation may facilitate secondary host immune responses (Segers and Lebeer, ; Vargas García et al ., ; Tytgat et al ., ), the present findings highlight the multifunctional nature of the multimolecular Tad pili of bifidobacteria in which adherence/colonisation and epithelial proliferative signalling are distinct molecular processes.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental endophthalmitis initiated by B. cereus deficient in hemolysin BL (Callegan et al, 1999), phosphatidylinositol-specific phospholipase C (Callegan et al, 2002), phosphatidylcholine-specific phospholipase C (Callegan et al, 2002), quorum sensing (Callegan et al, 2003), or swarming (Callegan et al, 2006) were not controlled to the same degree as observed with pili-deficient B. cereus. Studies reported that the presence of pili enhanced the uptake of pneumococci and lactobacilli by macrophages (Orrskog et al, 2012 and Vargas Garcia et al, 2015). If this were the case in our model, one would expect the bacterial burden to be greater in eyes infected with pili-deficient B. cereus.…”
Section: Discussionmentioning
confidence: 99%
“…A number of bacterial species rely on pili as a virulence determinant for adherence to mucosal tissues, to tissues in areas of high fluid flow, and in establishment of biofilms (Axner et al, 2011, Danne and Dramsi, 2012, Mandlik et al, 2008, Melville and Craig, 2013, Romero, 2013, Scheewind and Missiakas, 2012, and Vengadesan and Narayana, 2011). Engagement of pili with components of innate immunity has also been suggested, potentially contributing to the acute inflammatory response (Barrochi et al, 2006, Bassett et al, 2013, Crotty Alexander et al, 2010, and Vargas Gardia et al, 2015). Budzik et al (2007, 2008, 2009a, and 2009b) have reported on the structure and assembly of pili on the surface of vegetative B. cereus , but a specific role for pili in B. cereus infections has not yet been ascribed.…”
Section: Introductionmentioning
confidence: 99%